2019
DOI: 10.1155/2019/3693140
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Vasculature and Thickness after Small Incision Lenticule Extraction with Optical Coherence Tomography Angiography

Abstract: Purpose. To evaluate the changes in retinal vessel density and thickness after small incision lenticule extraction (SMILE) with optical coherence tomography angiography (OCTA) in myopic patients. Methods. In this prospective study, SMILE surgeries were done in 46 eyes of 24 patients with spherical equivalent (SE) more than −6.0 diopters (D). Retinal vessel density and thickness at the macula and optic nerve were recorded with OCTA before and 1 day, 2 weeks, and 1 month after surgery. Intraocular pressure (IOP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(36 reference statements)
3
11
0
Order By: Relevance
“…Vessel density changes were assumed by the suction effects during surgery on the retinal microcirculation, and instantaneous changes in suction may cause ischaemia-reperfusion injury [ 11 ]. IOP elevation during surgery also caused a decrease in ocular blood flow [ 24 ]. In a study on healthy people by increasing IOP, researchers found that transient elevation of IOP altered optic nerve head topography [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vessel density changes were assumed by the suction effects during surgery on the retinal microcirculation, and instantaneous changes in suction may cause ischaemia-reperfusion injury [ 11 ]. IOP elevation during surgery also caused a decrease in ocular blood flow [ 24 ]. In a study on healthy people by increasing IOP, researchers found that transient elevation of IOP altered optic nerve head topography [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vessel density changes were assumed by the suction effects during surgery on retinal microcirculation, and instantaneous changes of suction may cause ischemia-reperfusion injury [9]. IOP Elevation during surgery also caused a decrease in ocular blood ow [24]. In a paper studied healthy people by increasing IOP, researchers found transient elevation of IOP altered optic nerve head topography [25].…”
Section: Discussionmentioning
confidence: 99%
“…Vessel density changes were assumed by the suction effects during surgery on the retinal microcirculation, and instantaneous changes in suction may cause ischaemia-reperfusion injury [11]. IOP elevation during surgery also caused a decrease in ocular blood ow [24]. In a study on healthy people by increasing IOP, researchers found that transient elevation of IOP altered optic nerve head topography [25].…”
Section: Discussionmentioning
confidence: 99%